Numerical Evaluation of Thermal Comfort and Indoor Air Quality in an Office Space Equipped with a Radiant Ceiling Cooling System and Hybrid Radiative-Convective Cooling System - Mohammad Amini; Asgar Minaei; Negin Moallemi Khiavi (مجله مدل سازی در مهندسی)
In the present paper, the performance of radiant ceiling and hybrid radiative-convective cooling systems in terms of thermal comfort and indoor air quality in an office space have been numerically evaluated by ANSYS Airpack software. Due to the non-uniformity of the environment equipped with radiant ceiling cooling system, the main purpose of this research is to evaluate the standard thermal comfort indexes for individual bodey parts. According to the results, for the radiant ceiling cooling system, at ceiling temperatures of 18°C and 19°C, the overall thermal comfort indexes of PMV (Predicted Mean Vote) and PPD (Predicted Percentage of Dissatisfied) are in the acceptable range of -0.5<PMV<+0.5 and PPD<10%. However, these indexes increased as the ceiling temperature increased from 20°C to 26°C, resulting in a feeling of hotness. The overall thermal comfort indexes of the hybrid radiative-convective cooling system have been reduced in comparison with the radiant ceiling cooling system at all ceiling temperatures and under all air inlet conditions, so that the overall thermal comfort indexes according to ISO 7730 standard and ASHRAE/ANSI standard 55 are within the permissible range even at temperature of 20 ℃. The local thermal comfort indexes DR (Draught Rating) and PD (Percentage of Dissatisfied) of both systems were within permissible limits, thus local thermal discomfort cannot threaten the resident. Also, a hybrid radiative-convective cooling system leads to higher indoor air quality than a radiant ceiling cooling system.